Systemic bioavailability of fluticasone propionate administered as nasal drops and aqueous nasal spray formulations - Daley-Yates, Peter T (Blackwell Science Inc, 2001)
AIMS: To measure and compare the systemic bioavailability of fluticasone propionate aqueous nasal spray and a new nasal drop formulation, using a sensitive analytical method and high dose regimen. METHODS: Volunteers received four 800 µg doses of fluticasone propionate as a nasal spray or drops over 2 days, separated by an 8 h dose interval. On day 2, blood samples were collected for assay of fluticasone propionate plasma concentrations. RESULTS: The mean systemic exposure, for both formulations was 8.5 pg ml(−1) h (drops) and 67.5 pg ml(−1) h (spray). Mean absolute bioavailabilities were estimated to be 0.06% (drops) and 0.51% (spray), by reference to historical intravenous data. CONCLUSIONS: Both formulations exhibited low systemic bioavailability, even at 12 times the normal daily dose. The bioavailability from the nasal drops was approximately eight times lower than from the nasal spray.